2000
DOI: 10.1007/s002689910075
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the Gastric Cardia: Surgical Practices and Short‐term Operative Results in a Defined Swedish Population

Abstract: Adenocarcinoma of the gastric cardia has one of the most rapidly increasing incidence rates of all tumors in Western countries. The aim of this population-based investigation was to study surgical practices and postoperative morbidity and mortality during routine hospital care. The study comprised 176 patients given a new diagnosis of adenocarcinoma of the gastric cardia from February 1, 1989 to the January 31, 1995 in five Swedish counties. The tumor was resectable in 100 (57%) patients (in 36% of the women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Adenocarcinoma of the gastric cardia has a poor prognosis (11). Although 60-80% of the tumours are resectable, only 30% of them are at favourable stages I or II (1,8,12).…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma of the gastric cardia has a poor prognosis (11). Although 60-80% of the tumours are resectable, only 30% of them are at favourable stages I or II (1,8,12).…”
Section: Discussionmentioning
confidence: 99%
“…(2) If there were metastases to the lymph nodes at the splenic hilus or along the splenic artery. Based on the developmental anatomy, Lin [7] reported that by removal of the pancreatic body and tail, spleen and stomach en bloc with a cutting out of the pancreas at the junction of the head and body, he was able to completely provide dissection of the lymph nodes at the splenic hilus and along the splenic artery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore a total or partial resection of the invaded organs was necessary to obtain a curative resection [2] . The second reason was to facilitate more extensive regional lymph node dissection involving mainly the lymph node stations 10 and 11 and the pancreas and spleen.…”
Section: Discussionmentioning
confidence: 99%